Cranioplasty Following Decompressive Craniectomy - Iaccarino, Corrado; Kolias, Angelos G.; Roumy, Louis-Georges; Fountas, Kostas; Adeleye, Amos Olufemi (Frontiers in Neurology, 2020)
Cranioplasty (CP) after decompressive craniectomy (DC) for trauma is a neurosurgical procedure that aims to restore aesthesis improve cerebrospinal (CSF) dynamics and provide cerebral protection. In turn, this can facilitate neurological rehabilitation and potentially enhance neurological recovery. However, CP can be associated with significant morbidity. Multiple aspects of CP must be considered in order to optimize its outcomes. Those aspects range from the intricacies of the surgical dissection/reconstruction during the procedure of CP, the types of materials used for the reconstruction as well as the timing of the CP in relation to the DC. This article is a narrative mini-review that discusses the current evidence base; and suggests that no consensus has been reached about several issues, such as an agreement on the best material for use in CP, the appropriate timing of CP after DC, and the optimal management of hydrocephalus in patients who need cranial reconstruction. Moreover, the protocol-driven standards-of-care for traumatic brain injury (TBI) patients in high-resource settings are virtually out of reach for low-income countries, including those pertaining to CP. Thus there is a need to design appropriate prospective studies in order to provide context-specific solid recommendations regarding this topic